Автоматичний контроль концентрації та кислотності живильного розчину в гідропонних теплицях - Синявський, О. Ю.; Савченко, В. В. (Енергетика і автоматика, 2017)
AUTOMATIC CONTROL OF CONCENTRATION AND ACIDITY OF A NUTRIENT SOLUTION IN HYDROPONIC GREENHOUSESA. Sinyavsky, V. Savchenko Now in vegetable growing of closed soil the production of vegetables on small-scale substrates has become widespread, which makes it possible to more accurately and quickly adjust the parameters of the root environment.With hydroponic technologies, all the necessary mineral substances of the plant are derived from the nutritional solution, therefore, the deviation of the acidity and the concentration of mineral elements in it from optimal values lead to a violation of the absorption of nutrients and water by plants, which can lead to plant diseases and their death.In practice, the weekly control and adjustment of the nutrient solution based on analyzes performed by the agrochemical laboratory, does not allow maintaining the acidity and concentration of nutrient solution at an optimal level.The purpose of the study is to develop a system for automatic control of the concentration and acidity of the nutrient solution during the cultivation of plants in greenhouses using the hydroponic method.Nutrient solutions have a low overall concentration. The range of changes in the concentration of individual elements is also not great. Therefore, we can assume that the degree of electrolytic dissociation is unchanged, and the electrical conductivity is close to one.Specific electrical conductivity of the solution depends on the chemical composition and concentration of the elements that are part of its composition. At the same time, there is no unambiguous relationship between the specific electrical conductivity and the concentration of the solution.If the relationship between salt concentrations in a solution is known, then the specific conductivity is directly proportional to the total concentration of the solution and is uniquely determined by it.To measure the specific conductivity of nutrient solutions it is advisable to use contact conductivity analyzers. The static characteristic of the conductivity meter is linear, and the acceleration characteristic is approximated by the aperiodic link of the first order.On the basis of production tests, a method of calibration of conductivity meters in hydroponic greenhouses for grading 0,01 N, 0,02 N and 0,05 N potassium chloride, whose specific electrical conductivity is respectively 0,141, 0,277 and 0,667 S/m, was developed.To determine the acidity of the nutrient solution it is necessary to use industrial pH-meters.The static characteristic of the industrial pH-meter is linear, and the acceleration characteristic is approximated by the aperiodic link of the first order.On the basis of production tests, a method of calibration of industrial pH-meters for buffer solutions, having pH values at a temperature of 25 °C, was developed at 4.01, 6.86 and 8.93.